Mutation of the methylentetrahydrofolate reductase gene and its assosiation with changes in mood - Guillen, Anlly María; Etchelecu, Carolina (International Journal of Neurology, 2025)
The C677T mutation in the MTHFR gene (Methylenetetrahydrofolate reductase) reduces the activity of the enzyme responsible for converting folic acid (vitamin B9) into its active form, methylfolate, which is essential for the synthesis of neurotransmitters like serotonin, dopamine, and norepinephrine. This reduction can predispose individuals to mood disorders such as anxiety, irritability, or depression, particularly in situations of high stress, poor diet, or vitamin B deficiencies. The decreased enzymatic activity in this case can lead to less efficient production of neurotransmitters, affecting mood regulation and emotional well-being. However, these individuals often respond well to methylfolate supplementation, which helps compensate for the metabolic deficiency, improving chemical balance in the brain and reducing mood-related symptoms. Additionally, maintaining a diet rich in natural folates (found in leafy green vegetables) and other B vitamins can be helpful in minimizing the negative effects of polymorphism.